2014
DOI: 10.1016/j.ijsu.2014.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic common bile duct exploration versus pre or post-operative ERCP for common bile duct stones in patients undergoing cholecystectomy: Is there any difference?

Abstract: A best evidence topic in surgery was written according to a structured protocol. The question addressed was: in patients with symptomatic gallstones and concomitant common bile duct (CBD) stones, is a single-stage surgical strategy (laparoscopic cholecystectomy (LC) with common bile duct exploration) preferable, or a two-stage procedure involving LC with pre or post-operative endoscopic retrograde cholangiography (ERCP)? Two hundred and six papers were found using the reported search, of which four presented t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 9 publications
3
44
0
1
Order By: Relevance
“…Re-intervention within 90 days after the first procedure of stone extraction is associated with a 14-fold increased risk of death (27), which underlines the importance of a successful first therapeutic strategy for avoiding residual and recurrent choledocholithiasis. (28,29). Furthermore, LCBDE is an effective technique for choledocholithiasis with a proven safety and excellent outcome for elderly patients (30).…”
Section: Discussionmentioning
confidence: 99%
“…Re-intervention within 90 days after the first procedure of stone extraction is associated with a 14-fold increased risk of death (27), which underlines the importance of a successful first therapeutic strategy for avoiding residual and recurrent choledocholithiasis. (28,29). Furthermore, LCBDE is an effective technique for choledocholithiasis with a proven safety and excellent outcome for elderly patients (30).…”
Section: Discussionmentioning
confidence: 99%
“…There are now a sufficient number of studies to determine that there is no significant difference in clinical outcomes77 117 118 between LBDE and laparoscopic cholecystectomy combined with preoperative or postoperative ERCP. Studies have shown that single-stage LBDE is associated with a reduction in overall hospital stay and cost compared with the two-stage approach of ERCP and laparoscopic cholecystectomy 119 120.…”
Section: Surgical Management Of Cbdsmentioning
confidence: 99%
“…5 However, managing CBD stones remains controversial, with the debate between a single-stage procedure in the form of laparoscopic common bile duct exploration (LCBDE) with cholecystectomy and two-stage procedure using endoscopic retrograde cholangio pancreatography (ERCP) either before or after cholecystectomy. 6 The utilization of LCBDE is gradually increasing and is being accepted for CBD clearance; it is associated with reduced hospital stay compared to preoperative ERCP followed by laparoscopic cholecystectomy. 7 However, as LCBDE needs more advanced laparoscopic skills, and manipulation of the flexible choledochoscpe, the preferred procedure in many hospitals remains to do ERCP either before or after laparoscopic cholecystectomy.…”
Section: Introductionmentioning
confidence: 99%